Routledge handbook of craft and sustainability in India - Reubens, Rebecca; Kachru, Tanishka (London Routledge, 2025)
Traditional crafts have been an essential part of Indian history, culture and life. This handbook looks at craft as both a cultural artefact that reflects people's worldviews, indigenous practices and traditions, as well as a source of income generation and development that is inclusive.
Keywords: Traditional crafts; Indian history; Culture-India